EA LEVEL AND GLOBAL EARTH TEMPERATURE CHANGES HAVE COMMON OSCILLATIONS - Zotov, L. V. (Одеські астрономічні публікації, 2013)
Singular Spectrum Analysis (SSA) of Global Mean Sea Level (GMSL) and Global Average Earth Temperature (HadCRUT4) data revealed presence of quasiperiodic components with periods of 60, 20 and 10 years in both time series. 60-year component of sea level is anticorrelated with long-periodic changes in temperature, while 10 and 20-year components are correlated. The question what can be the nature of these common oscillations is discussed.